Evolution and population genomics of the Lyme borreliosis pathogen, Borrelia burgdorferi. Issue 4 (April 2015) - Seifert, Stephanie N.; Khatchikian, Camilo E.; Zhou, Wei; Brisson, Dustin
Highlights The complicated ecology and evolutionary history of the Lyme disease pathogen can be resolved using population genomics. Population genomics provides the power to detect fine-scale evolutionary processes, including horizontal gene transfer. Population genomic analyses can identify genes underlying ecologically relevant traits, including adaptations to host species. Correlating ecological and environmental parameters with demographic history can elucidate the causes of the recent re-emergence of Lyme disease.